Spider Silk Biomimetics Programs to Inform the Development of New Wearable Technologies - Blamires, Sean J.; Spicer, Patrick T.; Flanagan, Patricia J. (Frontiers in Materials, 2020)
Wearable fabrics are predominantly produced from synthetic polymer fibres derived from petrochemicals. These have negative effects on the natural environment as a consequence of the manufacturing process, insurmountable waste production, and persistence of the fibres in ecosystems. With the use of wearables worldwide set to increase exponentially, more environmentally friendly fibres are sought. Natural fibres such as spider silk are produced using proteins in a water solvent, yet they have many superior qualities to synthetic fibres. Moreover, spiders can tune their silk properties as their ecological circumstances demand it. Research focused on the biomimetic potential of spider silks with an eye on the development of smart wearable fibres is accordingly a potentially lucrative area of research. There are nonetheless major challenges associated, including recovering the original mechanical performance within the fibres developed, scaling up production, keeping the production costs of the silk building blocks to a minimum, elucidating and understanding the different silk genome sequences, and creating precision artificial spinning processes. We outline herein a template for a working framework for a spider silk biomimetics program that can inform designers and biological researchers alike. It suggests that an objective-focused research program utilizing a cross-disciplinary toolbox of top-down and bottom-up techniques is required. We close by providing some speculative examples stemming from current activities in our laboratories.